Occurrence, Composition, and Relationships in Marine Plastic Debris on the First Long Beach Adjacent to the Land-Based Source, South China Sea - Peng Zhang; Shan-Shan Wei; Ji-Biao Zhang; Zhou Ou; Yu-Qin Yang; Ming-Yue Wang (Journal of Marine Science and Engineering, 2020)
Land-based sources are the key sources of plastic debris, and mismanaged plastic debris can eventually enter the ocean via marine beaches. In this study, the spatial distribution and amount of plastic debris in the land-based source input zone of First Long Beach (FLB), China, which is a major tourist attraction, were first investigated. By using field investigation, sand samples were collected from two sections on FLB adjacent to land-based sources in December 2019, and the plastic debris in the sand samples was quantified and characterized in the laboratory. The amount of plastic debris ranged from 2 to 82 particles/m2 on this marine sand beach. There was a significant difference in plastic debris amount between the transects along the land-based source input zone (p < 0.05) due to the impacts of wind, ocean currents, and waves. The most abundant size of plastics was 0.5–2.5 cm (44.4%). Moreover, the most common color was white (60.9%). The most abundant shape of plastic debris fell into the fragment category (76.2%). The plastic debris amounts were significantly correlated with multiple sizes. Our results show that land-based wastewater discharge is a large plastic debris source on FLB under coastal water tide variation. Reduction strategies should be carried out by tracing the various land-based sources of plastic debris.